Genealogy Of The Prophet: Reassessing Ibn Saʿd’s Qur’anic Reference In Sira Nabawiyya - Ahmad Sanusi Azmi; Norazmi Anas; Amran Abdul Halim; Mohd Nor Adzhar Ibrahim; Khairul Aiman Wan Mokhtar (International Journal of Religion, 2024)
Non-Indexed Publication